Comparative Transcriptome Analysis of Gleditsia sinensis Thorns at Different Stages of Development - Feng Xiao; Yang Zhao; Xiurong Wang; Yanan Sun (Plants, 2023)
G. sinensis thorn (called “zào jiǎo cì”, ZJC) has important medicinal and economic value, however, little is known about the molecular mechanisms behind the development of ZJC. In this study, we measured the content of soluble sugar and starch during the growth and development of the thorn, and performed transcriptome sequencing of the thorn segment, non-thorn segment, apex, and root tip at five distinct stages of thorn formation. The results showed that, with the growth of ZJC, the soluble sugar content of the roots, hypocotyls, thorn stems, thornless stems, leaves, and the starch content of the roots and leaves all firstly increased and then decreased after the basic structure of thorns was formed; the soluble sugar content and starch content of ZJC showed an overall downward trend (decreased by 59.26% and 84.56%, respectively). Myb-like, YABBY2, Growth-regulating factor 3, TCP2, Zinc transporter 8, and another 25 genes may be related to the maintenance and growth of thorns. Gene Ontology (GO) enrichment analysis of differentially expressed genes (DEGs) between stems with thorn and thorn-free stems found that a significant number of DEGs were annotated with terms related to the positive regulation of development, heterochronic (GO:0045962), the positive regulation of photomorphogenesis (GO:2000306), and other biological process (BP) terms. The developmental initiation regulation of ZJC may be regulated by TCP transcription factors (TFs). Eight genes were selected randomly to validate the RNA-seq results using real-time quantitative PCR (RT-qPCR) and they indicated that the transcriptome data were reliable. Our work provided a comprehensive review of the thorn development of G. sinensis.